Dual-Parameter Sensing With a Single Supermode Interferometer - Flores-Bravo, Jose A.; Villatoro, Joel (Frontiers in Sensors, 2022)
Optical fiber interferometers have intrinsic sensitivity to temperature, thus, in practical applications; they need a reference temperature sensor or a mechanism to control the temperature. Here, we demonstrate that a single multicore fiber interferometer can monitor two parameters simultaneously; more particularly, refractive index and temperature. The interferometer is easy to manufacture; a short segment of an optical fiber with seven coupled cores is fusion spliced at the distal end of a conventional single mode optical fiber. In the coupled-core fiber, two supermodes beat; this makes the reflection spectrum of the device to exhibit a well-defined series of maxima and minima. The refractive index of a sample in contact with multicore fiber alters the amplitude of the interference pattern and temperature induces a shift to such a pattern. The changes of the interference pattern are easy to monitor and decode with a low-resolution spectrometer. As an application of our dual-parameter sensor, the thermo-optic coefficient of a sample was measured.